Exciting dynamic anapoles with electromagnetic doughnut pulses - Raybould, Tim (2017)
As was predicted in 1995 by Afanasiev and Stepanovsky, a superposition of electric and toroidal dipoles can lead to a non-trivial non-radiating charge current-configuration, the dynamic anapole. The dynamic anapoles were recently observed first in microwave metamaterials and then in dielectric nanodisks. However, spectroscopic studies of toroidal dipole and anapole excitations are challenging owing to their diminishing coupling to transverse electromagnetic waves. Here, we show that anapoles can be excited by electromagnetic Flying Doughnut (FD) pulses. First described by Helwarth and Nouchi in 1996, FD pulses (also known as “Flying Toroids”) are space-time inseparable exact solutions to Maxwell's equations that have toroidal topology and propagate in free-space at the speed of light. We argue that FD pulses can be used as a diagnostic and spectroscopic tool for the dynamic anapole excitations in matter.